A Tripp to the London National Gallery - Jacobs, Carol (Filozofski vestnik, 2017)
“A Tripp to the London National Gallery” takes up W. G. Sebald’s 1993 “Like Day and Night: On the Pictures of Jan Peter Tripp.” This is a piece of writing by a wildly popular “novelist” that normally escapes the notice of his readers. At the end of the essay Sebald reproduces Tripp’s large painting “Déclaration de guerre,” and declares it of a visual complexity not to be described in words, an exemplum, then of the incommensurability between language and objects of sight. The joke is, in an essay as riddled with jokes as it is with puzzles, that the answers to the riddles he poses materialize only when the large canvas, “Déclaration de guerre,” is cited by Tripp in another painting. The essay on Jan Peter Tripp gathers together in something of a jumble, a dizzying series of questions on the work of art: as preserving life, as recording history, as a reminder of its own materiality, and yet again as a bit of a prank, all under the guise of commentary. This is one of the most profoundly literary performances in Sebald’s works, despite its pretentions to be something else, and one of the most subtle theoretically.